Factors Influencing Injury Severity in Alcohol-Related Crashes: A Neural Network Approach Using HSIS Crash Data - Banerjee, Snehanshu; Khadem, Nashid K (ITE journal, 2019)
The phenomenon and aftermath of traffic crashes have long been recognized as convoluted events involving interactions between numerous factors related to the driver, traffic characteristics, roadway characteristics, and the environment. The severity of injuries in motor vehicle crashes is of considerable interest to policymakers and safety specialists. In the United States, fatality and injury rates for road traffic crashes have become a crucial subject. According to the Insurance Institute for Highway Safety, there were 34,439 fatal motor vehicle crashes in the US in 2016, resulting in 37,461 fatalities--1,450 of which occurred in North Carolina, USA. Twenty-four percent of these fatal crashes were alcohol-impaired driving crashes. A number of factors can potentially affect injury severity in a crash, alcohol consumption being one of them. Safety has always been a big concern for transportation engineers, transportation planners, safety agencies, federal agencies, and state agencies.